SELF- ASSESSMENT IN ENGLISH FOR PRESENTATION - Arni Sukmiarni (Jurnal Sastra - Studi Ilmiah Sastra, 2023)
This study explores self-assessment in English for Presentation as a subject course. The objective is to examine how students in the English for Presentation Class evaluate their own performance. The self-assessment criteria provided to the students consist of a series of questionnaires focusing on aspects such as voice usage—covering word stress, sentence stress, intonation, and chunking—as well as presentation structure and signposting. The study involves participants enrolled in the online English III course, English for Presentation, a mandatory subject at a private higher educational institution in Bandung, Indonesia. Data were collected through questionnaires completed by participants by the end of the course term. The finding indicates that the most of participants expressed positively towards self-assessment regarding the implementation of self-assessment, and the content they learned in English for Presentation: Voice Usage as pronunciation features and Presentation skills.